2020
DOI: 10.21037/qims.2020.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Implant placement accuracy in total knee arthroplasty: validation of a CT-based measurement technique

Abstract: Background: The primary goal of many computer-assisted surgical systems like robotics for total knee arthroplasty (TKA) is to accurately execute a preoperative plan. To assess whether the preoperative plan was executed accurately in 3D, one option is to compare the planned and postoperative implant placement using a preoperative and postoperative CT scan of the patient's limb. This comparison requires a 3D-to-3D surface registration between the preoperative and postoperative 3D bone models and between the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…36 While the CT-based measuring technique was questioned, Campanelli et al demonstrated that the measurement error of this technique was maximum 0.9 mm and 0.6°. 37 Because the impact of cutting errors was excluded in the work of Dahabreh et al, the mismatch could be a result of intraoperative registration errors as confirmed by our results. Given the observed errors and the cumulative behaviour in the surgical procedure, the intraoperative registration error should not be neglected and can be relevant for the total implant positioning error.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…36 While the CT-based measuring technique was questioned, Campanelli et al demonstrated that the measurement error of this technique was maximum 0.9 mm and 0.6°. 37 Because the impact of cutting errors was excluded in the work of Dahabreh et al, the mismatch could be a result of intraoperative registration errors as confirmed by our results. Given the observed errors and the cumulative behaviour in the surgical procedure, the intraoperative registration error should not be neglected and can be relevant for the total implant positioning error.…”
Section: Discussionsupporting
confidence: 82%
“…While the CT‐based measuring technique was questioned, Campanelli et al. demonstrated that the measurement error of this technique was maximum 0.9 mm and 0.6° 37 . Because the impact of cutting errors was excluded in the work of Dahabreh et al., the mismatch could be a result of intraoperative registration errors as confirmed by our results.…”
Section: Discussionsupporting
confidence: 78%
“…0.6 mm, which is finer than most clinical imaging protocols. Likewise, implant-induced metal artifacts cause uncertainty in alignment measures [24,25]. A study by Sires and Wilson [17] found absolute differences between resection angles measured intraoperatively and the corresponding implant alignments measured using a CT scan ranged from 1.09 ± 0.75 to 1.97 ± 1.41 for tibial coronal and sagittal alignment, respectively, with 9% of the accuracy measurements deviating by >3 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported comparable or decreased number of outliers with RATKA. However, in those studies, the accuracy and measurements were performed on standardized radiographs, which introduces a low reproducibility with known inaccuracies when compared with CT‐based measurements [5, 8]. To the best of our knowledge, the present trial is the first study that used CT‐based measurement techniques to determine implant placement accuracy for TKA with the use of 3D‐to‐3D surface registration between the perioperative planned and postoperative achieved implant placement in a prospective RCT comparing image‐free RATKA with CTKA.…”
Section: Discussionmentioning
confidence: 99%